Charge transport through nucleic acids - Wong, Jiun Ru (2016)
Electronic coupling of the stacked heterocyclic base pairs in DNA duplexes makes DNA a promising biomaterial for conducting electrons. The process, DNA-mediated charge transport (CT), has recently show pivotal biological functions in repairing/damaging DNA and signaling proteins via one-electron oxidation over long genomic distance. Utilizing various DNA model systems, several mechanistic features of DNA CT had been defined. However, details of how CT is affected by (1) alternative DNA structures (DNA vs DNA/RNA hybrid duplex) in a fast time scale and (2) external physical interference (magnetic field) have not been well investigated. Considering the sensitivity of CT towards base pair stacking and the reciprocal interferences between electronic and magnetic fields (MF), it is of great interests to explore how these factors may affect charge transport in DNA. In order to probe the CT phenomena in DNA, chemically modified G and A were developed as fast traps and incorporated into DNA duplex. Specifically, our investigation had shown that the efficiency of long-range hole and electron transport in DNA was dependent on the duplex structures, integrity of base pair stacking and magnetic field strength on a fast time scale. Differences in efficiency observed between DNA and DNA/RNA duplex can be accounted for by differences in stacking and conformational motions while spin evolution of the injected hole and the rearrangement of base pairs necessary for conformationally gated CT during charge migration were proposed to be the factors that MF assist in facilitating DNA-mediated CT. Herein, our results may open a new avenue for designing biomolecular wire based nanodevices and further understand the biological consequence of DNA-mediated charge transport.